ANALISIS ANGGARAN ALOKASI DANA DESA (ADD) DALAM PENILAIAN KEMAMPUAN PEMBIAYAAN PEMBANGUNAN DESA DI DESA MUARA TELADAN KECAMATAN SEKAYU KABUPATEN MUSI BANYUASIN. - Septariani, Jumania (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the extent to which the Village Fund Allocation (ADD) is able to finance Government Development, especially in Muara Teladan Village, Sekayu District, Musi Banyuasin Regency. This research was conducted in Muara Teladan Village, Sekayu District, Musi Banyuasin Regency, the data used in this study were data from 2013-2015. Data collection techniques used were field studies by conducting interviews with the head of Muara Teladan Village, direct observation in Muara Teladan Village and documentation in the form of financial documents such as the accountability report for Village Fund Allocation (ADD) in 2013-2015 and included literature study as a guide in this research ..The analysis shows that the implementation of the ADD budget in Muara Teladan Village in terms of planning, budgeting, and financing in village development for physical development has been effective even though non-physical development has not been achieved to the maximum. This indicates that the ability of its human resources as object and subject of the program village fund allocation is still not ripe.